A study on the readiness of building owner in enhancing building performance by embracing green building concept / Wan Nur Farahin Wan Ismail - Wan Ismail, Wan Nur Farahin (2015)
The retrofit project involves an existing facility because it provides a lot of advantages. Working in an existing facility, in turn, imposes constraints on the owners, operators, designers and constructor (Victor, 1990). The honorable Prime Minister of Malaysia in his speech at the United Nations Framework on Climate Change Coference (Conpenhagon Summit) has stated the commitment of Malaysia to reduce the carbon dioxide emission by as much as 40% compared to 2005 levels (Hamid, 2011). For this reason, low carbon retrofitting of the existing building is a vitally important factor in the transition. Although green building is good but there are many obstacles to face, as admitted by Davis (2001) that towards client knowledge, product sourcing and builder incentives. Analysis of the critical factors identified in the literature state that clients play a huge role in the successful completion of projects, as they are the ones with the funds (Nwachukwu, 2009). Therefore, this paper studies on a readiness of building owner in enhancing building performance by embracing green building concept by identifying barrier & challenging in transforming existing building to green building and levels of readiness of building owner towards green building. Methodology used in quantitative methods and analyzed by using SPSS software. Questionnaires had been distributed to the owners of shoplots in Sri Iskandar, Perak and Kota Bharu, Kelantan. From the studies done, the majority of the owners of the shoplot disagree to retrofit their existing building into green building. This happens because of lack of communication between government and public where the information about green building is not being distributed wisely.